EXPLORING SPATIAL PATTERNS OF URBAN BROWNFIELDS: THE CASE OF DAUGAVPILS CITY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
Deindustrialization has been an important process in transforming the urban regions in Central and Eastern Europe. In Daugavpils, there is a long history of industry dated back to the 19th century. The massive deindustrialization of the 1990s caused increased concentrations of brownfield localities within the city. Previous studies have demonstrated that the geographic location of urban brownfields is an important factor affecting brownfields regeneration. The aim of the current study is to explore the characteristics of the brownfield sites and their spatial patterns in the city of Daugavpils. The analysis is based on a data obtained during the fieldwork. The results presented in this paper depends on survey of 61 brownfield sites in Daugavpils. Majority of local brownfields are abandoned buildings previously used for industrial and commercial activities and unevenly distributed within the city. Higher number of brownfield regeneration have been detected in densely built-up areas close to the inner-city areas, while lower rates were found for areas with low population density at the periphery of the city. The findings also suggest that urban brownfield regeneration increases the attractiveness and livability of a particular locality.